The Effect of Using What Is It? Technique on Students’ Writing Achievement and Their Motivation - Fatimah Mulyani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The purpose of the study was to find out the effect of using What is it? Technique on students’ writing achievement and their motivation on descriptive paragraphs at state Junior High School 1 Kampar. This study was an experimental research which was intended to find out the effect of using What is it? Technique on the students’ writing achievement and their motivation. The participants of the study comprised 57 students found in 2 classes randomized from seven classes. Treatment by using What is it? Technique was given to an experimental class (n=29) but a control class (n=28) was not given treatment by using What is it? Technique. Data were collected using a writing test for writing achievement and a questionnaire for writing motivation. The data were analyzed by using inferential statistics. The findings showed that there was a significant effect of using What is it Technique on their achievement in writing descriptive paragraphs and there was a significant effect of using What is it? Technique on their motivation in writing descriptive paragraphs.